2020
DOI: 10.1186/s12958-020-00613-z
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of Diane-35 and metformin improves the ovulation in the PCOS rat model possibly via regulating glycolysis pathway

Abstract: Background: Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disease with unknown pathogenesis. However, the treatment of Diane-35 combined with metformin can improve the endocrine and ovulation of PCOS. In this study, we investigated the effects of Diane-35 combined with metformin (DM) treatment on ovulation and glucose metabolism in a PCOS rat model. Methods: Sprague Dawley rats were divided into 3 groups, control group, model group (PCOS group) and Diane-35 combined with metformin (PCOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…In the current study, rats with letrozole exposure showed PCOS-like reproductive and metabolic phenotypes compared with the controls. Consistently with previous study (27) A successful PCOS model was crucial for the continuation of the study. In our study, letrozole treated rats showed increased body weight, and PCOS-like reproductive and metabolic phenotypes, including signi cant alters in serum T, E2, LH, FSH and P, impaired insulin resistance and widespread metabolic abnormalities, as well as disrupted estrous cycles and poly ovaries.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, rats with letrozole exposure showed PCOS-like reproductive and metabolic phenotypes compared with the controls. Consistently with previous study (27) A successful PCOS model was crucial for the continuation of the study. In our study, letrozole treated rats showed increased body weight, and PCOS-like reproductive and metabolic phenotypes, including signi cant alters in serum T, E2, LH, FSH and P, impaired insulin resistance and widespread metabolic abnormalities, as well as disrupted estrous cycles and poly ovaries.…”
Section: Discussionsupporting
confidence: 88%
“…Rats exposed to letrozole in this study showed PCOS-like reproductive and metabolic phenotypes in contrast to the controls. Similar to a previous study (24), we established a PCOS-IR animal model using continuous letrozole administration through a slow-release implant. This model was used to further investigate the effects of metformin on the offspring of animals with PCOS-IR.…”
Section: Discussionmentioning
confidence: 98%
“…Another popular PCOS treatment (metformin and Diane-35 (cyproterone acetate and ethinyl estradiol)) has been shown to normalise ATP and lactate levels and increase expression levels of glycolysis-related rate-limiting enzymes (PKM2 (pyruvate kinase isozyme M2 isoform) and LDH-A) and NAD + -dependent deacetylase SIRT1 (silent information regulator 1) [ 87 ]. SIRT1 maintains blood glucose levels via the regulation of gluconeogenic/glycolytic pathways in the liver and improves oxidative stress-related insulin resistance [ 88 ].…”
Section: Pcos Treatments: Classical and Modern Mitochondria–oriented Approachesmentioning
confidence: 99%